Seismic processed data (Ocean Bottom Hydrophone working area dataset) of RV SONNE during cruise SO297, Taltal Ridge, Chile - Arne Warwel; Dietrich Lange; Anke Dannowski; Heidrun Kopp (PANGAEA, 2025)
The data comprises processed active-source seismic data acquired with ocean bottom hydrophones (OBH). The data were collected at the Taltal Ridge during expedition SO297 with the research vessel RV SONNE (doi:10.48433/cr_so297) offshore Taltal, north-central Chile (map for further details). The entire data set consists of 16 OBH stations. Seismic data were shot across the OBH along one profile. Each OBH consists of 1 channel (hydrophone).